Fast and optimised design of a differential VCO using symbolic technique and multi objective algorithms. Issue 8 (12th November 2019) - Panda, Madhusmita; Kumar Patnaik, Santosh; Kumar Mal, Ashis; Ghosh, Sumalya
Abstract : In this work, a DVCO has been designed for a 4‐bit, 10 MHz VCO based ADC. The noise modelling and analysis of this designed DVCO is carried out using layered determinant expansion based DDD technique. The results obtained using these methods are found to be nearly identical to that of SPICE. However, the computational time has been reduced from 13.7 sec using numerical method (SPICE) to 4.5 sec using DDD technique. Optimisation of the designed DVCO is then carried out using multi‐objective optimisation techniques such as IDEA and MOPSO to enhance the performance. Low power and low phase noise at the desired frequency of oscillation were the optimisation goals. For this designed DVCO, IDEA optimisation approach seems to be more efficient than the MOPSO. The optimised DVCO is then simulated at different process corners using SPICE. The designed DVCO has shown improvement in phase noise from −80.3 dBc/Hz to −88.9 dBc/Hz at 1 MHz offset. The power consumption is also reduced from 38.4 mw to 34.5 mw and achieved a target frequency of 3.49 GHz. These improvements in the performance of the DVCO lead to an improvement in the ENOB from 3.6 to 4.2 bit of the designed ADC.